Conceptualising the role of information and communication technologies in the design of higher education teaching models used in the UK. (5th December 2013) - Caird, Sally; Lane, Andy
Abstract Despite the widespread availability of information and communication technologies (ICTs) and some research into specific pedagogical practices using them, there has been little research on the role of these technologies in shaping broader pedagogical approaches in higher education (HE). Increased experimentation in using ICTs raises questions about their pedagogical role in teaching, learning and assessment provision, and in creating innovative pedagogies. An accepted approach is needed to compare the different ways ICTs and rich media are used in HE teaching models. Within the SusTEACH HE sustainability research project this was needed to support the carbon‐based environmental assessment of HE courses using ICTs. Building on a review of learning design theories and models, and ICTs used for pedagogical purposes, this paper considers several approaches to conceptualising the role of ICTs in HE courses, leading to the development of the Teaching Models Rating Tool designed to examine the role of ICTs in course provision. This tool characterises courses as using Face‐to‐Face Teaching Models, Distance Teaching Models, ICT‐Enhanced Blended Teaching Models or Online Teaching Models. Whilst this tool was designed to support research on sustainable HE teaching models in the UK, it has wider applications to support comparative assessments of pedagogical and economic impacts. Further developments will be informed by the complex and evolving role of ICTs in HE teaching models.